APLIKASI PUPUK HAYATI MIKORIZA DALAM MENINGKATKAN FASE PERTUMBUHAN VEGETATIF DAN GENERATIF KACANG TANAH (Arachis hypogea L.) - Fahrizal Hazra; Fatimah Nur Istiqomah; Rafid Nanda Saputra (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2023)
Peanut has long been cultivated in Indonesia and is generally grown on dry land. The continuous use of inorganic fertilizers can have a negative impact on the soil, so there is a need for environmentally friendly fertilizers such as biological fertilizers. This study aimed to elucidate the effect of mycorrhiza biofertilizer on the vegetative and generative growth of peanuts. The study was conducted in the experimental field of Cikabayan IPB with a three-factor Completely Randomized Design. The treatments tested were 1) control, 2) 100% NPK fertilizer, 3) 100% organic fertilizer, 4) 100% organic fertilizer + NPK, 5) 5 g mycorrhizae, 6) 100% NPK + mycorrhizae 5 g, 7) 100% organic fertilizer + mycorrhiza 5 g, and 8) organic fertilizer + NPK 100% + mycorrhiza 5 g. Parameters observed included plant height, number of primary branches, number of pods, pod weight, colonization or root infection, number and types of spores. The results showed that the application of NPK fertilizer + organic fertilizer + mycorrhizae 5 g could increase vegetative and generative growth in peanut plants. The treatment of NPK+ organic fertilizer + mycorrhizae 5 g (AOM) had a very high percentage of infection, which was 86.67%. The AOM treatment had a high number of spores, which was 32 spores and 3 types of spores were successfully associated, namely Acaulospora sp1, Acaulospora sp 2 and Glomus etunicatum.